(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Background: Influenza is a contagious respiratory illness caused by influenza virus that infects nose, throat and lungs. A surveillance study is undergoing in Dhaka National Medical College to characterize the clinical features of influenza viral illness. Objective: To recognize the diversity of strain of influenza virus in circulation in this part of country. Methodology: This prospective surveillance study is undergoing from June 2007. Cases are selected from among the patients visiting this hospital with fever and cough. Throat swab and nasal swab specimens are tested for presence of various influenza virus subtypes. Result: Between June 2007 to March 2012 we collected specimen from 1054 patients. Among them 141 (13.4%) were positive for influenza virus. 87 (62%) cases were influenza type A and 54 (30%) were type B. Among the 87 influenza A cases, 15 (17%) were A/H1, 24 (28%) were A/H, and novel A/H1 (Pandemic H1 N1) were 48 (55%). None of our cases were H5 N1 (Bird-Flu). Conclusion: This study confirms that influenza is prevalent in this region, causing considerable morbidity and hospital care. J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 23-24